2015
DOI: 10.1021/jf5056584
|View full text |Cite
|
Sign up to set email alerts
|

Egg Yolks Inhibit Activation of NF-κB and Expression of Its Target Genes in Adipocytes after Partial Delipidation

Abstract: How composition of egg yolk (EY) influences NF-κB, a key transcription pathway in inflammation, remains unclear. We performed partial delipidation of EY that removed 20–30% of cholesterol and triglycerides. The resulting polar and non-polar fractions were termed EY-P and EY-NP. NF-κB activation in response to EY from different suppliers and their fractions was examined in 3T3-L1 adipocytes using a NF-κB response element reporter assay and by analyzing expression of 248 inflammatory genes. Although EY-P and EY … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…These methods all have their own advantages and disadvantages . Some researchers have demonstrated that EYO possesses indeed some biological activities with regard to alleviating inflammation and promoting wound healing. , …”
Section: Biological Activities Of Egg Yolk Oilmentioning
confidence: 99%
“…These methods all have their own advantages and disadvantages . Some researchers have demonstrated that EYO possesses indeed some biological activities with regard to alleviating inflammation and promoting wound healing. , …”
Section: Biological Activities Of Egg Yolk Oilmentioning
confidence: 99%
“…Traditionally in Iran, people believed that egg yolk oil, which is extracted by direct heat possesses, has analgesic and anti-inflammatory properties (11), yet its mechanism as an anti-inflammatory agent is unclear. A study by Shen Q. et al claimed that egg yolk affects the NF-κB level in the inflammatory procedure, which is a major regulator in the transcription pathway (12). Following a partial delipidation process, egg yolk composition includes polar and nonpolar fractions.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the cholesterol and polyunsaturated fatty acids content of egg yolk suppress the pro-inflammation pathways. In fact, the activation of NF-κB (a key regulator of acute and chronic inflammation) is affected by egg yolk ingredients (12). Hence, egg yolk could be defined as an appropriate drug choice in the treatment of an anal fissure.…”
Section: Introductionmentioning
confidence: 99%
“…NanoString’s nCounter analysis (NanoString Technologies) system performed direct detection of target molecules from a single sample using color-coded molecular barcodes, giving a digital quantification of the number of target molecules as described before [35]). A custom panel containing axon guidance molecules was designed and used for simultaneous quantification of 32 axon guidance genes and 5 housekeeping genes.…”
Section: Experimental and Methodsmentioning
confidence: 99%